Implementing Task-Based Instruction in the Primary EFL Classroom: A Narrative Literature Review - Kalayo Hasibuan; Dian Adelia Putri; Parasetya Harahap; Chintya Wimanda (ANTHOR: Education and Learning Journal, 2026)
Task-Based Instruction (TBI) has become one of the most widely discussed approaches in English as a Foreign Language (EFL) teaching due to its emphasis on meaningful communication and learner-centered activities. This narrative literature review aims to examine the implementation of Task-Based Instruction in primary EFL classrooms and explore its impact on language learning outcomes, student engagement, and teaching practices. The study reviews recent national and international literature published between 2023-2025. The findings indicate that Task-Based Instruction promotes active participation, enhances communicative competence, increases learner motivation, and facilitates the development of integrated language skills. The review also reveals several challenges in implementation, including teachers’ limited understanding of task design, classroom management difficulties, assessment issues, and curriculum constraints. Furthermore, the integration of technology and authentic learning materials has been shown to strengthen the effectiveness of task-based instruction in primary education settings. The study concludes that Task-Based Instruction is a promising pedagogical approach for young EFL learners when supported by adequate teacher training, instructional resources, and contextual adaptation.